(untitled) (De Rebus Antiquis, 2020)
By the time the Aeneid was composed, between the years 29 and 19 BC, the memory of the divinization of Caesar was present, throwing the expectation on the Consecratio the Emperor himself. In the epic poem, the harbinger of the apotheosis of Augustus appears in the same prophecy that Jupiter ensures to Venus the reception of her son, Aeneas, among the immortals (Virgil, Aeneid, I.259-289). This theme reappears in Ovid’s Metamorphoses whose final lines of the fifteenth book portrays the transformation of Julius Caesar in astro - Sidus - and mention the date on which the Princeps should receive in heaven, the prayers of the governed (Ovid. Metamorphoses, XV.745-879). In view of the institution of imperial cult, we will investigate in the works listed the relationship between myth, memory and power in the Principate.